Green Recyclable Supported-Metal Catalyst for Useful Organic Transformations - C. Ranu, Brindaban; Bhadra, Sukalyan; Saha, Debasree (Current Organic Synthesis, 2011)
One of the major challenges confronted by modern chemists is the development of sustainable chemistry to maintain environmental chastity. With this perspective in mind, heterogeneous organometallic chemistry has been intensively investigated in recent times. The advantages offered by the heterogeneous catalysts are ease of separation of product, reusability of the catalyst, improved efficiency, eco-compatibility and economic feasibility. This review focuses on the application of heterogeneous catalysis in different synthetic approaches. The review consists of six units namely, palladium mediated reactions, copper mediated reactions, ruthenium mediated reactions, rhodium mediated reactions, multimetallic catalytic systems and supported catalysts for asymmetric transformations, which cover almost all sorts of latest developments in organic transformations promoted by immobilized transition metal catalysts. The discussion not only involves the illustration of efficiency and reusability but also highlights the scope and limitations associated with the supported catalytic systems from a green chemistry standpoint.
Keywords: catalytic activity